1998
DOI: 10.1021/bi972791w
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction and Characterization of a Dimeric Non-Zinc Glyoxalase I from Escherichia coli:  Evidence for Optimal Activation by Nickel Ions,

Abstract: The ubiquitous glyoxalase system converts toxic alpha-keto aldehydes into their corresponding nontoxic 2-hydroxycarboxylic acids, utilizing glutathione (GSH) as a cofactor. The first enzyme in this system, glyoxalase I (GlxI), catalyzes the isomerization of the hemithioacetal formed nonenzymatically between GSH and cytotoxic alpha-keto aldehydes. To study the Escherichia coli GlxI enzyme, the DNA encoding this protein, gloA, was isolated and incorporated into the plasmid pTTQ18. Nucleotide sequencing of the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
148
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(163 citation statements)
references
References 63 publications
14
148
1
Order By: Relevance
“…After extensive dialysis of the recombinant protein to remove loosely bound metals, 0.9 mol of nickel and 0.1 mol of zinc per mole of GLO1 dimer were detected by atomic absorption spectrophotometry. This stoichiometry suggests that one active site in the homodimeric protein does not tightly bind metal cofactor, an observation also made with the E. coli enzyme (7).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…After extensive dialysis of the recombinant protein to remove loosely bound metals, 0.9 mol of nickel and 0.1 mol of zinc per mole of GLO1 dimer were detected by atomic absorption spectrophotometry. This stoichiometry suggests that one active site in the homodimeric protein does not tightly bind metal cofactor, an observation also made with the E. coli enzyme (7).…”
Section: Resultssupporting
confidence: 53%
“…GLO1 is a metalloenzyme that isomerizes the glutathione hemithioacetal to S-D-lactoylglutathione through proton transfer to a metalbound enediol intermediate (5). This metal cofactor is zinc in eukaryotes but nickel in Escherichia coli (6,7). The difference in cofactor dependence is reflected in differences between the active sites of the human and E. coli enzymes, suggesting that the latter may be a target for antimicrobial therapy (8,9).…”
mentioning
confidence: 99%
“…This information provided structural confirmation of previous biophysical studies that indicated that Glo1 maintains an octahedral metal coordination environment, with metal-bound H 2 O/OH -also participating (55)(56)(57). Although also expecting the isolated Escherichia coli Glo1 to be a Zn 2+ -activated enzyme, a surprising metal activation profile was observed for this enzyme, drastically different from previously studied Glo1 (58). A narrower metal activation profile was observed for the E. coli Glo1, with Ni 2+ reconstitution providing the most active enzyme.…”
Section: Glo1contrasting
confidence: 53%
“…However, the coordination geometry was found to be close to trigonal bipyramidal, with only one H 2 O/OH -bound to the zinc center. Subsequent studies by nuclear magnetic resonance spectroscopy (NMR) elaborated on the inequivalence of the two active sites in the E. coli enzyme, accounting for previous solution studies (58,62,63). Additional studies on substrate thiol structure-function activities and kinetic isotope effects were reported for the E. coli Glo1 (64).…”
Section: +mentioning
confidence: 99%
“…1B). For example, GloI from human and yeast (4) and Plasmodium falciparum (5) prefers Zn 2ϩ , whereas GloI from several bacteria such as Escherichia coli (6) and Yersinia pestis, Pseudomonas aeruginosa, and Neisseria meningitidis (7) and from the protozoan parasite Leishmania major (8,9) is optimally activated in the presence of Ni 2ϩ . GloI from human (10,11) and E. coli (12) is active as a homodimer.…”
mentioning
confidence: 99%